THE INFLUENCE OF DIGITAL COMPETENCY AND SOCIAL MEDIA ON GENERATION Z'S CAREER CHOICES WITH SELF-EFFICACY AS AN INTERVENING VARIABLE - Egis Amanda; Khairawati; Marbawi; Chalirafi (PT. Radja Intercontinental Publishing, 2026)
This study aims to analyze the influence of digital competency and social media usage on Generation Z career choices with self-efficacy as a mediating variable in final year students of the Faculty of Economics and Business, Malikussaleh University. This study is motivated by the rapid development of digital technology that has changed the way Generation Z obtains information, develops competencies, and determines career choices. Amidst the increasing demands of the world of work for digital skills, students are required to have adequate digital competencies and be able to utilize social media effectively to support their career development. The method used in this study is a quantitative approach with data analysis techniques using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). Data were obtained through the distribution of online questionnaires to 184 final year students of the Faculty of Economics and Business, Malikussaleh University who met the research criteria. The results of the study indicate that digital competency has a significant effect on self-efficacy and career choices of Generation Z. The use of social media has a significant effect on self-efficacy, but does not have a significant effect on career choices of Generation Z. In addition, self-efficacy has a significant effect on career choices of Generation Z. The results of the mediation test indicate that self-efficacy partially mediates the effect of digital competency on career choices of Generation Z, and fully mediates the effect of social media use on career choices of Generation Z. These findings indicate that increasing digital competency and effective use of social media can strengthen students' self-efficacy , which ultimately plays a role in supporting the process of determining career choices of Generation Z.